2021
DOI: 10.48550/arxiv.2108.09828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A puzzle solved after two decades: SN 2002gh among the brightest of superluminous supernovae

RΓ©gis Cartier,
Mario Hamuy,
Carlos Contreras
et al.

Abstract: We present optical photometry and spectroscopy of the superluminous SN 2002gh from maximum light to +202 days, obtained as part of the Carnegie Type II Supernova (CATS) project. SN 2002gh is among the most luminous discovered supernovae ever, yet it remained unnoticed for nearly two decades. Using Dark Energy Camera archival images we identify the potential SN host galaxy as a faint dwarf galaxy, presumably having low metallicity, and in an apparent merging process with other nearby dwarf galaxies. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…A review of the literature reveals that the brightest SLSNe reported have absolute magnitudes in the range of βˆ’22.0 mag 𝑀 abs βˆ’22.5 mag (Smith et al 2007;VreeswΔ³k et al 2014;Smith et al 2016;De Cia et al 2018;Smith et al 2018;Lunnan et al 2018;Cartier et al 2021;Yin et al 2021). Therefore assuming that UID 30901 reached one of the brightest maximum luminosities reported for a SLSNe (𝑀 π‘Ÿ β‰ˆ βˆ’22.5), we can place an approximate redshift upper limit of 𝑧 0.7 for this SN.…”
Section: Light Curve Comparisonmentioning
confidence: 68%
See 2 more Smart Citations
“…A review of the literature reveals that the brightest SLSNe reported have absolute magnitudes in the range of βˆ’22.0 mag 𝑀 abs βˆ’22.5 mag (Smith et al 2007;VreeswΔ³k et al 2014;Smith et al 2016;De Cia et al 2018;Smith et al 2018;Lunnan et al 2018;Cartier et al 2021;Yin et al 2021). Therefore assuming that UID 30901 reached one of the brightest maximum luminosities reported for a SLSNe (𝑀 π‘Ÿ β‰ˆ βˆ’22.5), we can place an approximate redshift upper limit of 𝑧 0.7 for this SN.…”
Section: Light Curve Comparisonmentioning
confidence: 68%
“…(Smith et al 2007). The time of maximum light for the PS1 and DES SNe was computed using Gaussian process interpolation as described in Cartier et al (2021), and the light curves were corrected by Galactic reddening (𝐸 (𝐡 βˆ’ 𝑉)) as reported by Schlafly & Finkbeiner (2011) using the Cardelli et al (1989) extinction law. For SN 2006gy the 𝐴 𝑅 values reported by Smith et al (2007) were used for the reddening correction, this is 𝐴 𝑅 = 0.43 and 𝐴 𝑅 = 1.25 for our galaxy and the SN host galaxy, respectively.…”
Section: Light Curve Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible energy sources to explain SLSNe (e.g., Wang et al 2019). One energy source model to account for the extra energy is a magnetar, i.e, a rapidly spinning-magnetic neutron star (NS) remnant of the core collapse supernova (CCSN; e.g., Greiner et al 2015;Metzger et al 2015;Kangas et al 2017;Kasen et al 2016;Chen et al 2017a;Mazzali et al 2017;Nicholl et al 2017;Yu et al 2017;Villar, Nicholl, & Berger 2018;Chatzopoulos & Tuminello 2019;Cartier et al 2021;Nicholl 2021;Gomez et al 2022; for a partial list of other energy sources see, e.g., Urvachev et al 2021 and.…”
mentioning
confidence: 99%